2022
DOI: 10.3390/cancers14225548
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus (MCPyV) and Cancers: Emergency Bell or False Alarm?

Abstract: Merkel cell polyomavirus (MCPyV), the sole member of Polyomavirus associated with oncogenesis in humans, is the major causative factor of Merkel cell carcinoma (MCC), a rare, neuroendocrine neoplasia of the skin. Many aspects of MCPyV biology and oncogenic mechanisms remain poorly understood. However, it has been established that oncogenic transformation is the outcome of the integration of the viral genome into the host DNA. The high prevalence of MCPyV in the population, along with the detection of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 166 publications
0
1
0
Order By: Relevance
“…Furthermore, MCPyV has also been detected in other neoplasms affecting the oral cavity and the gastrointestinal system, in lung, renal, prostate, and cervical cancer, as well as in skin samples collected from healthy individuals [123]. Regarding soft tissue neoplasms, some studies have reported the presence of MCPyV in different NMSCs, the majority represented by SCCs affecting immunosuppressed patients, but also in AK, atypical fibroxantoma, keratoacanthoma, Kaposi's sarcoma, porocarcinoma, and dermatofibrosarcoma, despite the relatively low viral load and the lack of viral integration into the host genome having raised the question as to its possible coincidental rather than causal role in the genesis of such cancers [124][125][126].…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…Furthermore, MCPyV has also been detected in other neoplasms affecting the oral cavity and the gastrointestinal system, in lung, renal, prostate, and cervical cancer, as well as in skin samples collected from healthy individuals [123]. Regarding soft tissue neoplasms, some studies have reported the presence of MCPyV in different NMSCs, the majority represented by SCCs affecting immunosuppressed patients, but also in AK, atypical fibroxantoma, keratoacanthoma, Kaposi's sarcoma, porocarcinoma, and dermatofibrosarcoma, despite the relatively low viral load and the lack of viral integration into the host genome having raised the question as to its possible coincidental rather than causal role in the genesis of such cancers [124][125][126].…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%